Renewed Possibilities: Showcasing the Lived Realities of Black Girls using Ethnopoetics. Issue 1 (1st March 2022) - Smith, Dywanna
Abstract: In this article, I explore how ethnopoetics can be a profound research methodology and can also offer a pathway to self-actualization. When ethnopoetics is combined with a Black feminist/womanist theoretical framework, it allows for Black girls to self-define and self-validate their existence. The verse novel provides an opportunity to communicate Black girls' and women's feelings and experiences to researchers and educators in accessible ways. It also serves as a platform to grieve, praise, love, and grow. Such work stands in marked contrast to dominant narratives of Black girlhood.